2020
DOI: 10.3390/ani10111976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Glutamine Supplementation on Early Postnatal Muscle Morphology in Low and Normal Birth Weight Piglets

Abstract: Adapted nutrition can improve the growth of low birth weight (LBW) piglets. Since maternal milk is thought to provide insufficient glutamine (Gln) for LBW piglets, the current study investigated the influence of Gln supplementation during the early suckling period on development and lipid deposition in skeletal muscle. The weight differences between LBW and normal birth weight (NBW) littermates persisted from birth to slaughter (p < 0.001). However, intramuscular Gln and Ala concentrations were altered in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 63 publications
5
25
1
Order By: Relevance
“…Results of total lipid droplet area in muscle fibers and in adipocytes were reported in our former publication (5). We observed more lipid droplets in LBW piglets than in their NBW littermates at 5 dpn.…”
Section: Lipid Droplets and Adipocyte Size In M Longissimus And M Semitendinosussupporting
confidence: 81%
See 4 more Smart Citations
“…Results of total lipid droplet area in muscle fibers and in adipocytes were reported in our former publication (5). We observed more lipid droplets in LBW piglets than in their NBW littermates at 5 dpn.…”
Section: Lipid Droplets and Adipocyte Size In M Longissimus And M Semitendinosussupporting
confidence: 81%
“…Our previous study indicated a clear difference between LBW and NBW piglets in the abundance of lipid droplets within muscle fibers at 5 dpn ( 5 ). The area percentage of intramyocellular lipid droplets decreased during the first days of life by more than 80%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations